Online measurement of soil organic carbon as correlated with wheat normalised difference vegetation index in a vertisol field - Tekin, Yücel; Ulusoy, Yahya; Tumsavas, Zeynal; Mouazen, Abdul Mounem (Hindawi Publishing Corporation, 2014)
This study explores the potential of visible and near infrared (vis-NIR) spectroscopy for onlinemeasurement of soil organic carbon (SOC). It also attempts to explore correlations and similarities between the spatial distribution of SOC and normalized differential vegetation index (NDVI) of a wheat crop. The online measurement was carried out in a clay vertisol field covering 10 ha of area in Karacabey, Bursa, Turkey. Kappa statistics were carried out between different SOC and NDVI data to investigate potential similarities. Calibration model of SOC in full cross-validationresulted in a good accuracy ( 2 = 0.75, root mean squares error of prediction (RMSEP) = 0.17%, and ratio of prediction deviation (RPD) = 1.81). The validation of the calibration model using laboratory spectra provided comparatively better prediction accuracy ( 2 = 0.70, RMSEP = 0.15%, and RPD = 1.78), as compared to the online measured spectra ( 2 = 0.60, RMSEP = 0.20%, and RPD = 1.41). Although visual similarity was clear, low similarity indicated by a lowKappa value of 0.259 was observed between the online vis-NIR predicted full-point (based on all pointsmeasured in the field, e.g., 6486 points)map of SOC and NDVI map.